Antifungal Effect of Novel 2-Bromo-2-Chloro-2-(4-Chlorophenylsulfonyl)-1-Phenylethanone against Candida Strains - Staniszewska, Monika; Bondaryk, Małgorzata; Wieczorek, Magdalena; Estrada-Mata, Eine; Mora-Montes, Héctor M.; Ochal, Zbigniew (Frontiers in Microbiology, 2016)
We investigated the antifungal activity of novel a 2-bromo-2-chloro-2-(4-chlorophenylsulfonyl)-1-phenylethanone (compound 4). The synthesis of compound 4 was commenced from sodium 4-chlorobenzene sulfinate and the final product was obtained by treatment of β-chloro β-keto-sulfone with sodium hypobromite. The sensitivity of sixty three clinical isolates belonging to the most relevant Candida species towards compound 4 using the method M27-A3 was evaluated. We observed among most of the clinical strains of C. albicans MIC ranging from 0.00195 to 0.0078 µg/mL. Compound 4 at 32 μg/mL exhibited fungicidal activity against nine Candida strains tested using the MFC assay. Compound 4 displayed anti-Candida activity (with clear endpoint) against 22% of clinical strains of Candida. Under compound 4, Candida susceptibility and tolerance, namely paradoxical effect (PG), was found for only two clinical isolates (C. glabrata and C. parapsilosis) and reference strain 14053 using both M27-A3 and MFC method. We found that compound 4 does not induce toxicity in vivo against larvae of Galleria mellonella (≥97% survival) and it displays reduced toxicity on mammalian cells in vitro (<CC20 at 64 µg/mL). Furthermore, XTT assay denoted clear metabolic activity of sessile cells in the presence of compound 4. Thus the effect of compound 4 on formed C. albicans biofilms was minimal. Moreover, strain 90028 exhibited no defects in hyphal growth on Caco-2 monolayer under compound 4 influence at MIC= 16 µg/mL. The MIC values of compound 4 against C. albicans 90028, in medium with sorbitol did not suggest that compound 4 acts by inhibiting fungal cell wall synthesis. Our findings with compound 4 suggest a general strategy for antifungal agent development that might be useful in limiting the emergence of resistance in Candida strains.